2013
DOI: 10.1186/1471-2156-14-121
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into the genomic architecture of feed and nitrogen efficiency measured by residual energy intake and nitrogen excretion in growing pigs

Abstract: BackgroundImprovement of feed efficiency in pigs is of great economical and environmental interest and contributes to use limited resources efficiently to feed the world population. Genome scans for feed efficiency traits are of importance to reveal the underlying biological causes and increase the rate of genetic gain. The aim of this study was to determine the genomic architecture of feed efficiency measured by residual energy intake (REI), in association with production, feed conversion ratio (FCR) and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…In contrast to other studies that reported heritabilities of ADG and FCR in pigs ranging from 0.05 to 0.48 and 0.22 to 0.40 for ADG and FCR, respectively (Kavlak & Uimari, 2019; Nascimento, Nascimento, Dekkers, & Serão, 2019; Saintilan et al, 2013; Shirali, Varley, & Jensen, 2018; Silva, Lopes, Lopes, & Gasparino, 2019), our heritability estimate of ADG was close to zero and the one of FCR was rather low. Several QTLs were identified for ADG (Shirali et al, 2013; Silva et al, 2019) and FCR (Reyer et al, 2017; Silva et al, 2019), indicating a genetic basis of these traits. One possible reason why our estimates for ADG and FCR were comparably low could be the relatively small sample size of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies that reported heritabilities of ADG and FCR in pigs ranging from 0.05 to 0.48 and 0.22 to 0.40 for ADG and FCR, respectively (Kavlak & Uimari, 2019; Nascimento, Nascimento, Dekkers, & Serão, 2019; Saintilan et al, 2013; Shirali, Varley, & Jensen, 2018; Silva, Lopes, Lopes, & Gasparino, 2019), our heritability estimate of ADG was close to zero and the one of FCR was rather low. Several QTLs were identified for ADG (Shirali et al, 2013; Silva et al, 2019) and FCR (Reyer et al, 2017; Silva et al, 2019), indicating a genetic basis of these traits. One possible reason why our estimates for ADG and FCR were comparably low could be the relatively small sample size of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the costs involved in chemical analysis, the N and P contents in the empty body or the carcass are generally estimated. For instance, Saintilan et al (2013) used prediction equations that relate lean meat content during dissections to nitrogen or phosphorus excretion and Shirali et al (2013) used the deuterium dilution technique to estimate water content, from which lean meat content can be derived. Saintilan et al (2013) reported heritabilities of N and P retention between 36%–43% and 30%–41%, respectively, in a range of pig breeds.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that different genes can be associated with RFI at different stages of growth. Shirali et al (2013) showed that different QTL influence RFI at different stages of growth in growing-finishing pigs. In addition, Shirali et al (2014) reported that RFI at 60 to 90 kg BW was lowly correlated with RFI at 90 to 120 kg BW and 120 to 140 kg BW, supporting the findings of this study.…”
Section: Dynamic Genetic Background Of Feed Efficiencymentioning
confidence: 99%
“…This difference can be due to different definitions of feed efficiency and different methods of estimating correlations. Furthermore, feed efficiency has been shown to have different genetic backgrounds at different stages of growth in other species, for example in pigs (Shirali et al, 2014) and different genes responsible for efficiency of feed utilization at different stages of growth (Shirali et al, 2013). The phenotypic correlations between the growing and furring periods were positive and moderate to high and generally smaller than the genetic correlations, suggesting the effect of residual variance on the feed efficiency.…”
mentioning
confidence: 97%